Tolerância à salinidade induzida pelo ácido salicílico em sementes e plântulas de milho híbrido - Tonel, Fernanda Reolon (2011)
Several phenolic compounds are formed in plants secondary metabolism, such as salicylic acid which has a defensive function acting as an antioxidant agent under stress conditions. Therefore, the purpose in this research was to evaluate the influence of the sodium choride (NaCl) in three hybrid corn lots, as well as the salicylic acid (SA), as a reducer of the salinity effects. There have been used three corn seed lots for both of the experiments realized. In the first one, the seeds were exposed to concentratrions of zero, 30, 90 and 180 mM of NaCl. In the second one, the seeds were previously soaked for 60 minutes at two concentrations of salicylic acid (zero and 1mM) and soon after that subjected to concentrations of zero, 30, 90 and 180 mM NaCl. In order to determine the viability and vigor of seeds in these two experiments, the following tests were conducted: germination test, germination rate index, shoot and root seeds length, shoot and roots dry mass, electrical condutivity, seedlings growth in greenhouse, growth rate velocity in greenhouse, shoot and root seeds length and shoot and roots of seedlings dry mass. Taking into account the conditions in which the experiment was conducted it is possible to assume that the salicylic acid at concentrations of 1mM attenuates the effects caused by NaCl, when NaCl concentrations do not esceed 90 mM. However, it has a detrimental effect on the sedling root systems that were submitted to this teatment.